The effects of water and non‐nutritive sweetened beverages on weight loss during a 12‐week weight loss treatment program. (June 2014) - Peters, John C.; Wyatt, Holly R.; Foster, Gary D.; Pan, Zhaoxing; Wojtanowski, Alexis C.; Vander Veur, Stephanie S.; Herring, Sharon J.; Brill, Carrie; Hill, James O.
<x xml:space="preserve">Abstract</x> Objective To compare the efficacy of non‐nutritive sweetened beverages (NNS) or water for weight loss during a 12‐week behavioral weight loss treatment program. Methods An equivalence trial design with water or NNS beverages as the main factor in a prospective randomized trial among 303 men and women was employed. All participants participated in a behavioral weight loss treatment program. The results of the weight loss phase (12 weeks) of an ongoing trial (1 year) that is also evaluating the effects of these two treatments on weight loss maintenance were reported. Results The two treatments were not equivalent with the NNS beverage treatment group losing significantly more weight compared to the water group (5.95 kg versus 4.09 kg; P < 0.0001) after 12 weeks. Participants in the NNS beverage group reported significantly greater reductions in subjective feelings of hunger than those in the water group during 12 weeks. Conclusion These results show that water is not superior to NNS beverages for weight loss during a comprehensive behavioral weight loss program.